2017
DOI: 10.3382/ps/pew331
|View full text |Cite
|
Sign up to set email alerts
|

Color stability and lipid oxidation of broiler breast meat from animals raised on organic versus non-organic production systems

Abstract: The aim of the present research was to evaluate the influence of organic and non-organic production systems on color stability and lipid oxidation of broiler meat Pectoralis major (PM) stored under refrigeration (4°C) for 9 days. PM samples from organic (ORG) and non-organic (NORG) production systems were compared based on physicochemical analyses (instrumental color, myoglobin concentration, metmyoglobin reducing activity (MRA), pH, and lipid oxidation) performed in 4 different trials (n = 4). In general, NOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…However, Woo-Ming et al (2018) reported that access to pasture did not affect breast colour parameters in broiler chickens. Viana et al (2017) found that the a * value of broiler meat was higher in organic production, and the b * value was higher in conventional production.…”
Section: Discussionmentioning
confidence: 96%
“…However, Woo-Ming et al (2018) reported that access to pasture did not affect breast colour parameters in broiler chickens. Viana et al (2017) found that the a * value of broiler meat was higher in organic production, and the b * value was higher in conventional production.…”
Section: Discussionmentioning
confidence: 96%
“…The increase in lipid oxidation is potentially due to the depletion of meat redox capacity during storage and the formation of secondary products that interact with fatty acids, which can cause a chain reaction and intensify lipid oxidation (Chamorro et al, ). In general, the colour stability of meat appears related to lipid oxidation (Viana, Canto, Costa‐Lima, Salim, & Conte‐Junior, ). In addition, the micro‐organisms produce undesirable quality changes in meats, especially in relation to lactic acid bacteria, a major bacterial group associated with meat spoilage (Doulgeraki et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the discoloration of meat is also associated with increased in oxidative processes from lipid oxidation, for the formation of metmyoglobin. The accumulation of metmyoglobin, which could be due to the reduction of metmyoglobin reducing enzymes activity relates to color deterioration, which corresponds to more discoloration and changes in light reflectivity [25,26]. Meanwhile, the changes in the enzyme activity may also affect the increased redness value at frozen storage temperature compared with chilled temperature, and this corroborates with Fernandes et al [27], which demonstrated increase meat redness after being stored at frozen (−12 • C) compared with chilled (between 0 and 4 • C) temperature.…”
Section: Effects Of Different Storage Temperature and Storage Duratiomentioning
confidence: 99%